(untitled) (AYUSHDHARA, 2020)
Ovarian cysts are fairly common, fluid filled sacs that form in or on women’s ovaries. Symptoms of ovarian cyst depend to a large extent on the size of the cysts. Allopathic treatment includes combined oral contraceptive pills and if cyst appears to be growing after 3 months of usage of pills, therapy surgery like laparoscopy/laparotomy may be recommended. There are various adverse effects of contraceptive pills. Cyst in Ayurveda can be correlated with Granthi. Besides specific disease, the word Granthi has also been used in Sushrut Samhita, Madhavnidan, Bhavprakash and Yogratnakar. Chakrapani says that the disease has been named Granthi to denote the specific character i.e., glandular or nodular swelling. The disease Granthi can be equated with all types of small glandular or nodular swelling developing mostly due to benign tumours i.e. neoplasm and cysts. As the treatment for suppurated and inflamed Vataja, Pittaja and Medoja granthis as well as gentle massage to make Kaphaj Granthi soft is advised, thus these can be equated with cysts specially subcutaneous cysts. Here an effort was made to treat simple ovarian cyst of size 3.4 x 2.2cm using Ayurvedic treatment modalities, at the end of 74 days of treatment, Panchakarma procedure along with internal medication resulted in 100% improvement, and alleviated all associated symptoms.